Pengaruh Promosi Instagram dan Celebrity Endorsement Terhadap Keputusan Pembelian Geprek Bensu di Karawang - Muhamad Ari Maulana; Dede Jajang Suyaman (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to examine and analyze the effect of the Promotion of Instagram and Celebrity Endorsement on Purchasing Decisions. This study uses quantitative methods with descriptive and verification approaches. It found a sample of 100 people and a population of 1,730 using the Slovin formulas. The sampling technique used is purposive sampling. This study uses multiple regression analysis. The results of this study indicate partially Instagram promotion has a partial significant influence on Purchasing Decisions. Celebrity Endorsement does not have a partial significant effect on Purchasing Decisions. Simultaneously, the Promotion of Instagram and Celebrity Endorsement has a simultaneous influence on Purchasing Decisions by 60.1%.